2013
DOI: 10.1063/1.4800230
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulations of a single n-butanol drop rising in water

Abstract: The motion of an n-butanol drop in water under the influence of gravity was numerically studied using a diffuse interface free energy lattice Boltzmann method. A pure two-liquid system without mass transfer between the phases was considered. A range of drop diameters of 1.0–4.0 mm covered the flow conditions. Most calculations were carried out in a moving reference frame. This allowed studying of long-term drop behavior in a relatively small computational domain. The capability of the method to capture the dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
(101 reference statements)
1
9
0
Order By: Relevance
“…Watanabe and Ebihara [27] used two-component two-phase LBM to simulate the process of drop rising. Komrakova et al [28] performed numerical simulation of n-butanol drop rising in water using the multiphase LBM, the simulation results they obtained agree well with the experimental data.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Watanabe and Ebihara [27] used two-component two-phase LBM to simulate the process of drop rising. Komrakova et al [28] performed numerical simulation of n-butanol drop rising in water using the multiphase LBM, the simulation results they obtained agree well with the experimental data.…”
Section: Introductionmentioning
confidence: 67%
“…The heights of the computational domain were set to Reynolds number as derived from Clift et al [12] The steady state Reynolds numbers reported in Figure 2A are within 0.2% of = 5.6 so that the impact of height on rising velocity can be negligible, which is consistent with the three-dimensional simulation. [28] The flow map due to Clift et al [12] indicates a Reynolds number of 5.0 for the specific values for and where it should be noted that this map is based on (three-dimensional) experimental data.…”
Section: Domain Size Influencementioning
confidence: 99%
“…It can be seen that at the beginning of the circulating and oscillating regimes, the deviations of the VOF method are less than the level set. It has been previously reported that the simulation rise time of the study of Bertakis et al (2010), was too short to reach terminal velocity (Engberg and Kenig, 2014;Komrakova et al, 2013). They concluded that their large deviations from the Bertakis et al (2010) terminal velocity data were due to not considering a sufficiently long rise time in Bertakis et al (2010) for the oscillating large drops.…”
Section: Droplets Transient and Terminal Velocitiesmentioning
confidence: 90%
“…The different rise velocities had been previously shown by Wegener et al (2010). Komrakova et al (2013) studied the rising of n-butanol drops of 1-4 mm drop size range with both stationary and moving reference frame. Deviations of 5% for terminal velocities of smaller drops and up to 20% for large oscillating drops were reported using the Lattice-Boltzmann technique.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of the method was verified and then validated by simulation of the gravity‐driven rise of a single drop, drop deformation, and breakup in a simple shear flow . Then it was applied to simulations of liquid‐liquid dispersions .…”
Section: Introductionmentioning
confidence: 99%